A troubling cost—A study of the republican sacrifice in murals - Fredrika Larsson (Frontiers in Sociology, 2025)
This article explores the representation of the cost of war in mainstream and dissident republican murals in Northern Ireland by examining depictions of bodily sacrifice in three historical rebellions. The study highlights how psychological resilience is valorized alongside physical sacrifice, reinforcing identity hierarchies within republicanism. This challenges assumptions of republican solidarity, revealing competitive dynamics within and between mainstream and dissident factions. Murals as expressions of the republican identity and collective memory show how cultural violence is embedded in the republican collective memory, legitimizing past violence while marginalizing dissenting perspectives. This perpetuation hinders societal healing, as these narratives exclude those who challenge the justification of violence, complicating efforts to address the mental health crisis stemming from the Troubles. The article underscores the critical role of visual culture in shaping collective memory and identity, perpetuating societal hierarchies and cultural violence. It also identifies the potential for reinterpretation of sacrifice, offering a path toward inclusive understandings of the Troubles.